2020
DOI: 10.1097/prs.0000000000006836
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of the Trephined: Quantitative Functional Improvement after Large Cranial Vault Reconstruction

Abstract: Background: Large decompressive craniectomies may be life-saving; however, they may also result in syndrome of the trephined. This postrecovery sequela is characterized by dizziness, fatigue, depression, weakness, speech slowing, gait disturbance, and impaired mentation. Because this entity is poorly understood, the authors attempted to quantify the functional improvement in patients with syndrome of the trephined after cranial vault reconstruction. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
4
19
3
Order By: Relevance
“…www.nature.com/scientificreports/ performance recovery compared with those that underwent immediate cranioplasty following TBI. Both our current study and our human data demonstrate an association with unrepaired cranial defects and decreased motor performance 9 . Ex-vivo MRI demonstrated preserved cortical anatomy in the rats that underwent cranial repair following TBI which likely accounts for the improved motor performance when compared to TBI rats that underwent hemi-craniectomy.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ performance recovery compared with those that underwent immediate cranioplasty following TBI. Both our current study and our human data demonstrate an association with unrepaired cranial defects and decreased motor performance 9 . Ex-vivo MRI demonstrated preserved cortical anatomy in the rats that underwent cranial repair following TBI which likely accounts for the improved motor performance when compared to TBI rats that underwent hemi-craniectomy.…”
Section: Resultssupporting
confidence: 74%
“…These persistent deficits in the unrepaired rat calvarium (independent of TBI) mirror those seen in humans with SoT. In a recent publication by our group, 143 human subjects who underwent DC demonstrated a 28% incidence of SoT 9 . Of these 40 subjects with SoT, 70% demonstrated complete functional return on average 4.3 days following cranioplasty.…”
Section: Resultssupporting
confidence: 56%
“…Recent studies have shown an association between craniectomy size and SoT. [29,39] In a study by Tarr et al SoT incidence increased sharply when craniectomy area reached 50 cm 2 and beyond [39]. Although we did not nd a difference in mean craniectomy area between SoT and non-SoT group, the inclusion of only large craniectomies in our study (mean craniectomy area 112.8 ± 35.4 cm 2 ) limited the power to detect this association.…”
Section: Detailed Neurological Assessment Is Instrumental In Detecting Sotcontrasting
confidence: 57%
“…The main nding of this study is the high incidence of SoT in patients with large craniectomies, suggesting that the condition is underreported. [16,17,30,34,39] Contrary to previous studies we have identi ed that 65% patients suffered from SoT. A detailed prospective neurologic and radiologic assessment within four days before and after cranioplasty, allowed to identify the spectrum of SoT condition.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation